Polish Modernization in Biographical Films of the 2010s - Mazierska, Ewa Hanna (Załącznik Kulturoznawczy, 2022)
This article examines representation of the state socialist past in three Polish biographical films, made in the 2010s, Bogowie (Gods, 2014), directed by Łukasz Palkowski, Sztuka kochania (The Art of Loving, 2017), directed by Maria Sadowska and Ostatnia rodzina (The Last Family, 2017), directed by Jan P. Matuszyński. It argues that it them Poland is represented as a country trying to modernize itself and investigates how this modernization is achieved. It does so by locating these films in two contexts: the discourse of Poland’s modernization and biographical film.